Auctions for buying back groundwater for environmental purposes: Which design performs better?. (4th August 2021) - Lan, Le; Iftekhar, Md Sayed; Fogarty, James; Schilizzi, Steven
Abstract: Buyback auctions to reduce groundwater extraction for agriculture have been used in many real world scenarios but, to date, the impact of different auction design mechanisms for this context has not been comprehensively studied. Here, three auction design issues are studied: (i) framing the overall objective as either a budget constrained auction or a water target auction; (ii) the severity of budget and target constraints; and (iii) the role of a spatially explicit environmental benefit index. To answer the research questions an agent‐based optimisation model is developed for the most important groundwater system in Western Australia. The results show that a budget constrained auction performs as well or better than a target constrained auction and that use of an environmental benefit index improves auction efficiency.